A Comparative Analysis of Child Adoption without Court Decree and Child Adoption with Court Decree - Namira Dinda Pramesti; Nuria Siswi Enggarani (Universitas Muhammadiyah Surakarta, 2025)
The practice of child adoption in Indonesia varies in terms of its legal formalization, with some adoptions conducted through informal family arrangements and others established via Court Decrees. This legal variation raises questions concerning the validity and legal consequences of each method. This study aims to (1) compare child adoption without a Court Decree and adoption with a Court Decree, and (2) examine the legal implications of adoption conducted without formal judicial authorization. The research uses a qualitative normative legal method, focusing on statutory regulations and official legal frameworks. This article discusses two types of adoption procedures: one that follows a formal process through a Court Decree, and another that relies on informal familial agreements, both of which are governed under Government Regulation No. 54 of 2007 on Child Adoption. The findings show that legal provisions concerning family status, marriage, parental relationships, and adoption are regulated and protected under Law No. 1 of 1974 on Marriage. Child adoption may be undertaken by families with or without biological children, often to support family welfare and gender balance. Adoption through informal channels, although commonly practiced, carries different legal consequences compared to adoption formalized by a Court Decree. These findings highlight the importance of ensuring legal certainty and protection for all parties involved in the adoption process.